Pengaruh Lingkungan Kerja dan Standar Operasional Prosedur Terhadap Kinerja Pegawai pada KPPBC Tipe Madya Pabean B Kualanamu - Melinton Soritua Nababan (JOURNAL ECONOMICS AND STRATEGY, 2023)
This research aims to determine the influence of the work environment and standard operational procedures on employee performance at the Customs and Excise Supervision and Service Office Type Madya Customs B Kualanamu. The data used is primary data collected using a questionnaire with a Likert scale. The number of samples used was 37 employees from the total population. The data analysis technique used is multiple linear regression analysis. The results show that partially the work environment has a positive and significant effect, indicated by a sig value of 0.000 < 0.05. Standard operating procedures have a positive and significant influence on performance as indicated by a sig value of 0.000 < 0.05. Likewise, partially the work environment and standard operational procedures have a significant effect (sig value 0.000 < 0.05) on performance. The coefficient of determination (R2) is 0.585, meaning that the ability of work environment variables and standard operational procedures to explain variations in work quality is 58.5%. Meanwhile, another 41.5% is explained by other variables not explained in this study.